An Adolescent Boy with Systemic Toxicity Due to Smoke Inhalation - Chris Merritt; Frank Overly (Association of American Medical Colleges, 2014)
Abstract Introduction Burn management and airway management are commonly encountered in busy emergency departments, and although emergency airway management is a mainstay of care in critically burned patients, inhaled toxins may be less immediately considered. This simulation case is designed to help remind emergency physicians of the various ways that house fires can be deadly, focusing on inhaled toxins. The simulated patient in this scenario is free of external burns but nonetheless requires critical care and attention to the cellular asphyxiants that can be encountered in inhalational injuries. Methods This simulation scenario involves a 16-year-old boy suffering the ill effects of inhaled toxins, including carbon monoxide and cyanide. Learners must perform a rapid basic assessment for evidence of burn injuries, provide initial critical care, identify the likelihood of inhalation toxicity-both carbon monoxide and cyanide-and initiate directed therapy, including preparation for hyperbaric therapy and antidotes to cyanide. The case was developed using the Laerdal SimMan and associated software but can be easily adapted to a variety of low- or high-fidelity simulation manikins. Included in the case are the associated program files, PowerPoint slides, and pictures. The encounter should take approximately 15-20 minutes to complete. Results This case has been run with a cohort of pediatric emergency medicine fellows as active participants. A junior fellow was the primary learner in the case, with a senior fellow as a backup physician. Passive participants, including pediatric emergency medicine attending physicians and fellows, observed the simulation via video link and actively participated in the debriefing. In total, there have been four active learners and approximately 15 passive learners for the case. Both active and passive learners provided feedback, stating that the case was realistic and relevant to their learning. Discussion The case is most suitable for emergency medicine residents or pediatric emergency medicine fellows. With adjustments appropriate to the level of learner, it may also be targeted toward senior medical students, prehospital emergency personnel, or emergency medicine residents The focus on critical care and airway management suggests that use of the case could be suitable for senior pediatric residents or trainees in pediatric critical care, although it has not been piloted in these populations of learners.